Moral Education Against Gender Injustice in The Short Story of Perempuan Yang Terjerat Kursi Taman By Suta Sartika - Zakiya Ulhaq, Chanaya; Nurul Pajriah, Hanida; Nur Awaliyah, Melanti; Dzaka Ulfikri, Mohamad; Faris Mujahid, Salman; Azmi, Ulil (International Proceedings of Nusantara Raya, 2023)
Short stories are prose fiction which tells about an event that is experienced by the main character. Not just a story, in a short story there are many moral values in it. This research aims to analyze and describe the depiction of moral education on gender inequality in the short story Woman Trapped in Garden Chairs by Suta Sartika. This study uses a qualitative descriptive method, with data collection techniques and listening. steps research conducted, among others, by collecting data, reducing data, and analyze the data to describe the moral values contained in the short stories studied. The results obtained from research on the short story Women who are entangled in the garden chairs by Suta Sartika, namely, morals are something related to what is good and what is bad, about moral rights and obligations (morals), values about right or wrong that are held by society. Moral is a teaching about good and bad that is generally accepted as an act, attitude, obligation and others.